Catch me if you candy - Alexander, Ellie (Alexander, Ellie. Bakeshop mystery, 2023)
Things are getting spooky in Catch Me If You Candy, the next delicious installment in the Bakeshop Series from author Ellie Alexander, set in Ashland, Oregon! Halloween has arrived in picturesque Ashland, Oregon, and all of the ghouls and goblins have descended on Main Street for the annual parade. It's a giant street party and Torte is right in the mix. Jules Capshaw and her team have been baking up autumn delights and trick-or-Torte bags filled with sugar cookie cutouts, spiced cider, and mummy munch. It's the end of the season at the Oregon Shakespeare Festival, which means that the costumes for the parade are going to be out of this world. The elaborate guises even extend to pets. The grand marshal of this year's parade is no other than a regal pug aptly named King George. Jules is delighted to get to share the experience with Carlos and Ramiro, but things take a dark turn when she discovers a dragon slumped in front of the bakeshop. Jules is distraught when she realizes the dragon is dead. She's also shaken because a few days before the parade, her mother's Mahjong partner Helen discovered a warning note about a dragon in an antique game set. Jules hopes it's just a random coincidence, but as the clues begin to unfold it becomes evident that there's been a murder on All Hallow's Eve. Can Juliet sift out the truth before the killer comes after her?